In Vitro and In Vivo Antiplasmodial Activity of Three Rwandan Medicinal Plants and Identification of Their Active Compounds - Muganga, Raymond; Angenot, Luc; Tits, Monique; Frédérich, Michel (Planta Medica, 2014)
In our previous study, we reported the interesting in vitro antiplasmodial activity of some Rwandan plant extracts. This gave rise to the need for these extracts to also be evaluated in vivo and to identify the compounds responsible for their antiplasmodial activity. The aim of our study was, on the one hand, to evaluate the antiplasmodial activity in vivo and the safety of the selected Rwandan medicinal plants used in the treatment of malaria, with the objective of promoting the development of improved traditional medicines and, on the other hand, to identify the active ingredients in the plants. Plant extracts were selected according to their selectivity index. The in vivo antiplasmodial activity of aqueous, methanolic, and dichloromethane extracts was then evaluated using the classical 4-day suppressive test on Plasmodium berghei infected mice. The activity of the plant extracts was estimated by measuring the percentage of parasitemia reduction, and the survival of the experimental animals was recorded. A bioguided fractionation was performed for the most promising plants, in terms of antiplasmodial activity, in order to isolate active compounds identified by means of spectroscopic and spectrometric methods. The highest level of antiplasmodial activity was observed with the methanolic extract of Fuerstia africana (> 70 %) on days 4 and 7 post-treatment after intraperitoneal injection and on day 7 using oral administration. After oral administration, the level of parasitemia reduction observed on day 4 post-infection was 44 % and 37 % with the aqueous extract of Terminalia mollis and Zanthoxylum chalybeum, respectively. However, the Z. chalybeum extract presented a high level of toxicity after intraperitoneal injection, with no animals surviving on day 1 post-treatment. F. africana, on the other hand, was safer with 40 % mouse survival on day 20 post-treatment. Ferruginol is already known as the active ingredient in F. Africana, and ellagic acid (IC50 = 175 ng/mL) and nitidine (IC50 = 77.5 ng/mL) were identified as the main active constituents of T. mollis and Z. chalybeum, respectively. F. africana presented very promising antiplasmodial activity in vivo. Although most of the plants tested showed some level of antiplasmodial activity, some of these plants may be toxic. This study revealed for the first time the role of ellagic acid and nitidine as the main antimalarial compounds in T. mollis and Z. chalybeum, respectively.
Keywords: Fuerstia africana; Lamiaceae; Terminalia mollis; Combretaceae; Zanthoxylum chalybeum; Rutaceae; ellagic acid; nitidine; in vivo antiplasmodial activity